Stress and deformation analysis on dam spillway structure due to water discharge - Hassan N.H.; Zawawi M.H.; Abas M.A.; Radzi M.R.M.; Hassani A.; Zahari N.M.; Ramli M.Z.; Kamaruddin M.A.; Sidek L.M. (American Institute of Physics Inc., 2023)
This study assesses the structural analysis on the sector gate in dam spillway with 5m gap opening. The parameters determined on this study are equivalent stress and total deformation. The structure analysis on the spillway structure is due to the impact of water discharge. Computational fluid dynamic (CFD) modelling is applied to assess the water flow that affect stress and deformation occurred using computational aided program using ANSYS. Result of the transient structure model show that the highest stress value is at the radial gate which is 29.69MPa and the lowest stress value is at stilling basin which is 0.037 x 10-9 MPa. All the deformation values are relatively low especially at the stilling basin which is 1.021 x 10-9 m and the largest deformation value is at the radial gate which is 10.47 x 10-6m. It can be concluded that the stress and deformation give different result due to different materials. Stress and deformation values at mild steel material parts are higher than concrete material parts due to the high impact of water pressure. Future mitigation measures have to take to ensure the sustainability of the structural integrity. 2020 Author(s).